FAKTOR-FAKTOR PENYEBAB LEMAHNYA KEDUDUKAN KONSUMEN DIBANDINGKAN PELAKU USAHA DI INDONESIA - Wohon, Ernesta Uba; Tija, Laura Berenika Apriliani; Siwemole, Louise Mariano Ngiso Artono; Donpiera, Giovanni Lucianus M.; Wallep, Imanuel Markutoja (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The weak position of consumers against business actors is a very important issue in the context of consumer protection in Indonesia. Consumers are often at a disadvantage because business actors have greater economic power, information, and legal access. In today’s digital era and free market, consumer protection challenges are increasingly complex, especially with the emergence of digital products and services that are not yet fully regulated in consumer protection regulations. This can reduce consumer loyalty and damage the reputation of irresponsible business actors. The research method used in this research study is normative legal research. Thus, this research is very important because it aims to identify and analyze the factors that cause the weak position of consumers in relations with business actors in Indonesia. In addition, this research is also important because it aims to analyze the impact of the weak position of consumers on the national economic system and identify its influence on the level of public trust in business actors in Indonesia. By doing so, it is expected that the position of consumers in Indonesia can become stronger and optimally protected